Synthesis and Characterization of Hybrid Dimeric Steroid Spiroketals - Mayorquín-Torres, Martha C.; Maldonado-Domínguez, Mauricio; Flores-Álamo, Marcos; Iglesias-Arteaga, Martín A. (Synthesis, 2021)
The synthesis of six dimeric spiroketals bearing an estradiol half fused to the 5α- or 5β-epimers of androstane, cholestane, and spirostane nuclei is described. The synthetic procedure comprises the Sonogashira coupling of different steroid alkynes with 2-iodoestradiol 17-monoacetate, followed by Pd-catalyzed spiroketalization. The structural characterization of the obtained hybrid dimers was performed using a combination of 1D and 2D NMR techniques, and was assisted by DFT calculations. Single crystal X-ray diffraction of one of the obtained compounds confirmed the proposed structures.
Keywords: Sonogashira coupling; Pd-catalyzed spiroketalization; hybrid steroid dimers; NMR; X-ray diffraction; DFT-NBO calculations